Informacijski ambulantni podsistem kot nadgradnja bolnišničnega informacijskega sistema Kliničnega centra (BIS KC) - Grgič, Milan (Informatica Medica Slovenica, 2002)
For the needs of diagnostic neurophysiologic investigations performed at the UMC Institute of Clinical Neurophysiology (ICN), we constructed a local computer-based information system in 1994. The administrative as well as medical data have been collected in our laboratories and could be analysed or reviewed at any work station in the network. With the introduction of the UMC HIS in the year 2000, locally organised programs, covering only local needs, became redundant. On the base of the old one, we have created a new programme which runs in Windows and could be linked with the hospital information system.
Keywords: Ambulantna oskrba, informacijski sistemi; Ambulatory Care Information Systems; Computer Communication Networks; diagnostika; informacijski sistemi; Neurophysiology; Nevrofiziologija; Računalniške mreže; zdravstvo